PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) TERHADAP HASIL BELAJAR PASSING BAWAH BOLAVOLI (STUDI PADA SISWA KELAS X TPM 1 SMK PGRI 2 KOTA PASURUAN) - PRATAMA SARI, SABRINA (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Basically, physical education is a process of education through physical activity and also escalate physical ability. Learning process need variety learning model and attractive in order to raise happiness and joy so that the students are interest to and not being bored in the learning process. Based on researcher’s observation, in SMK PGRI 2 Pasuruan, students are tend to be idle and less teacher’s control in the learning process. The learning model which referred is cooperative learning type Number Hesd Together (NHT) in volleyball underpass learning outcomes.  This learning model is expected to indicate a maximum learning outcomes. This study aims to determine the effect of cooperative learning model type Numbered Head Together (NHT) toward volleyball underpass learning outcomes. This study is an expetimental research with descriptive quantitative approach. Sample of this study are 40 students. From the result of statistical calculation, it can be concluded that there is a significant effect in cooperative learning model type Numbered Head Together (NHT) toward volleyball underpass learning outcomes which come out from tcount value (15,8666) >ttable (2,032) with significant rate 0,05 while the effect is found to be 21,38%. Keywords: Cooperative learning type NHT, volleyball underpass, learning outcomes.